Identification of RAPD markers closely linked to the mlo-locus in barley - Manninen, O.M. (Blackwell Publishing Ltdcustomerservices@oxonblackwellpublishing.com, 1997)
Developing resistance to powdery mildew, Erysiphe graminis f.sp. hordei, is a major goal of many barley breeding programmes. Several resistance genes have been tagged or mapped with molecular markers. The mlo gene confers durable resistance towards all known isolates of the pathogen. In this study, RAPD markers and bulked segregant analysis were used to determine PCR-based markers linked to the mlo-locus. Sixty doubled haploid lines from a cross between an isogenic line of 'Ingrid' carrying the mlo11 allele and a susceptible cv. 'Pokko' were used as plant material. Seven linked RAPD markers were found, the closest lying 1.6 cM away from the resistance gene. When eight barley varieties were assayed for the presence of this band, F4-980, it was found in the resistant varieties but not in the susceptible ones. The linked marker bands could be amplified from DNA-samples prepared by using three different methods, including a quick squash technique. PCR-based markers linked to the resistance gene can be used as tools for selection in breeding programmes.